Statistical analysis of curing phenomenon of an epoxy adhesive. Issue 1 (1st October 2022) - Keerthana, S H; Mujeeb, A; Radhakrishnan, P
Abstract : Dynamic speckle imaging is one of the powerful optical techniques used for investigating the dynamical processes of biological as well as industrial materials. It is a cost effective technique and also non-invasive in nature. It possesses high temporal and spatial resolution. This paper reports the application of certain numerical algorithms for extracting the information regarding the curing process of an epoxy adhesive. Time evolution of speckle images were analyzed using statistical methods such as Normalized 2 dimensional Cross-correlation and Inertia moment. The Inertia moment was found to decrease and correlation coefficient was found to increase due to the fall in activity that resulted by the curing phenomenon. The curing time of epoxy is obtained as five minutes which is in accordance with the company literature.